Prehistoric Archaeolgy and National Education - Miles Crawford BURKITT (Zephyrus, 2009)
The scientific investigator is largely wasting his time if his results never become widely known and do not influence his generation. The same, of course, applies to the archaeologist. What is the good of accumulating collections if no one ever utilises them, or of making excavations if no one ever sees or hears of the results. Indeed actual damage is done because materials which might have been of importance to savants are withdrawn and become no longer available for study